Smoking and Desire to Quit Smoking Behavior in a Sample of Turkish Adolescents - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2015)
Introduction: The age of starting the habit of smoking, one of the top causes of many illnesses, is usually in the period of adolescence. This study was conducted to determine students' smoking status and to explore their desire to quit and their experiences during the cessation process. Methods: This descriptive study was performed with 934 adolescents between the ages of 14 and 20 years at a vocational high school located in Istanbul, Turkey. The data were collected by using a survey form. Results: The mean age of the adolescents was 16.38 +/- 1.12 years. Among the adolescents, 90.3% were male. Of the group, 29.9% reported that they had smoked at least once, and 12.1% of the participants smoked regularly. Among the students who smoked, 80% reported that they wanted to quit smoking. Among the smokers, 55.2% reported that they tried to quit smoking but could only stop smoking for a period of between 1 day and 1 month at maximum(71.4%). A group of 68.9% reported that they wanted to quit because they were afraid of getting sick in the future, 28.8% indicated economic reasons to quit smoking, and 24.2% reported that they wanted to stop smoking because they did not want to damage the environment. Conclusion: More than half of the smokers among the students had tried to stop smoking, but most of them had failed to quit. These results indicate that schools need programs for the cessation and the prevention of smoking.
Keywords: school health; school nursing; smoke cessation; smoking; HIGH-SCHOOL-STUDENTS; TRANSTHEORETICAL MODEL; CESSATION; CIGARETTE; SUSCEPTIBILITY; SMOKERS; STATES